Occurrence of Unexpected Adverse Reactions to Vaccines in Children with Mastocytosis - Hanna Abuhay; Alicia S. Clark; Melody C. Carter (Galenos Yayinevi, 2020)
Aim:Children with cutaneous or systemic mastocytosis may experience severe manifestations of mast cell mediator release including anaphylaxis. The perceived risk for adverse vaccine reactions creates concern among parents and pediatricians regarding modification of the routine vaccine schedule for safety.Materials and Methods:Using the National Institutes of Health (NIH) Biomedical Translational Research Information System and Clinical Research Information System, we conducted a retrospective chart review of 94 children ≤18 years of age, evaluated at NIH with mastocytosis. Based on the recommended childhood immunization schedule, we estimated that these 94 patients received approximately 2,136 vaccinations. Post vaccination reactions were determined as expected or unexpected according to the centers for disease control (CDC) parameters for vaccine-associated events.Results:Eighty-four patients (89.4%) had no reports of moderate-severe post-vaccination reactions. Eleven reactions after vaccination were reported in 10 of 94 patients (10.6%), of which four patients had unexpected reactions (4.3%). Unexpected reactions included facial swelling, flushing and exacerbation of skin lesions which are not reported as possible vaccine reactions by the CDC. One patient was treated for anaphylaxis 2 hours post-varicella vaccine administration. Five patients with a history of anaphylaxis and a mean tryptase level of 115 ng/mL did not report vaccine-induced reactions.Conclusion:Children with mastocytosis in this study did not experience a higher rate of adverse vaccine reactions compared to the general population. Anaphylaxis to other causes was not a risk factor for an untoward vaccine response. In patients that experience a severe postvaccination reaction such as anaphylaxis, a modified schedule with single vaccine administration is a safer approach.